Nanoscale self-organization and metastable non-thermal metallicity in Mott insulators - Ronchi, Andrea; Franceschini, Paolo; De Poli, Andrea; Homm, Pía; Fitzpatrick, Ann; Maccherozzi, Francesco; Ferrini, Gabriele; Banfi, Francesco; Dhesi, Sarnjeet S.; Menghini, Mariela; Fabrizio, Michele; Locquet, Jean-Pierre; et al. (Nature communications, 2022)
Mott transitions in real materials are first order and almost always associated with lattice distortions, both features promoting the emergence of nanotextured phases. This nanoscale self-organization creates spatially inhomogeneous regions, which can host and protect transient non-thermal electronic and lattice states triggered by light excitation. Here, we combine time-resolved X-ray microscopy with a Landau-Ginzburg functional approach for calculating the strain and electronic real-space configurations. We investigate V 2 O 3 , the archetypal Mott insulator in which nanoscale self-organization already exists in the low-temperature monoclinic phase and strongly affects the transition towards the high-temperature corundum metallic phase. Our joint experimental-theoretical approach uncovers a remarkable out-of-equilibrium phenomenon: the photo-induced stabilisation of the long sought monoclinic metal phase, which is absent at equilibrium and in homogeneous materials, but emerges as a metastable state solely when light excitation is combined with the underlying nanotexture of the monoclinic lattice. Mott metal-insulator transition in real materials is characterized by complex lattice and electron dynamics involving multiple length and time scales. Here, by combining time-resolved experimental probe and coarse-grained modelling, the authors elucidate the nanoscale dynamics across the Mott transition in V 2 O 3 .